Real-world patterns of immunoglobulin replacement therapy for infection prevention in common variable immunodeficiency: a multicenter nationwide study - Moral Moral, Pedro; Garcia-Bustos, Victor; Balastegui-Martin, Héctor; Martínez Mercader, Sandra; Bracke, Carmen; Mateu, Lourdes; Solanich, Xavier; Antolí, Arnau; Carrillo-Linares, Juan Luis; Robles-Marhuenda, Ángel; Puchades, Francesc; Pelaez Ballesta, Ana; et al. (Frontiers in Immunology, 2025)
Background and aimsImmunoglobulin replacement therapy (IgRT), administered intravenously (IVIg) or subcutaneously (SCIg), is the cornerstone treatment for patients with Common Variable Immunodeficiency (CVID). Although both modalities demonstrate similar efficacy, SCIg is associated with fewer systemic adverse events and increased patient autonomy. Despite these advantages, its utilization remains limited in certain regions, particularly in the Mediterranean region. This study aimed to evaluate real-world patterns of IgRT use in Spanish CVID patients and provide a comprehensive analysis of the factors associated with IVIg and SCIg administration in routine clinical practice.MethodsA cross-sectional, multicenter study was conducted using data from the GTEM-SEMI-CVID Registry, encompassing 212 adult CVID patients receiving IgRT across Spain. Patients were grouped based on the administration route: IVIg and SCIg. Demographic, clinical, and immunological data, including IgRT modality, dosage, administration setting, and comorbidities, were collected. Comparative statistical analyses were performed to identify differences between both treatment groups.ResultsOf the 212 patients, 58.5% received IVIg and 41.5% received SCIg. SCIg recipients were younger (47.5 vs. 54.8 years, p = 0.003) and predominantly treated at home (80.6% vs. 1.6%, p < 0.001), compared to those receiving IVIg. SCIg use was significantly higher in tertiary hospitals compared to secondary ones (44.4% vs. 17.4%, p = 0.0136). Infection rates, autoimmune comorbidities, weekly doses (7.2 g for IVIg vs. 7.7 g for SCIg, p = 0.142), and IgG trough levels were comparable across groups.ConclusionThis study provides real-world evidence on IgRT patterns in Spanish patients with CVID, revealing a marked increase in SCIg use over the past decade, although IVIg remains predominant, especially in secondary hospitals. Age significantly influenced the choice of modality, with IVIg preferred for older patients and SCIg for younger ones, while disease severity did not impact this decision. These findings underscore the need to optimize access to SCIg, particularly in secondary centers, to enhance patient autonomy and improve therapeutic outcomes.